Queneau en tchèque: la langue française parlée, écrite et traduite - Šotolová, Jovanka (Verbum – Analecta Neolatina, 2006)
A detailed analysis of the Czech translation of Raymond Queneau’s Chiendent shows many solutions that reveal possibilities of the use of similar methods in translation of spoken language in French and in Czech. First, we will try to sum up what problems the translation of Queneau’s texts bring up, as some of them stand on the very border of possibility of translation to a foreign language. We will also explore the question of whether the text of the translation preserves all the nuances of the original text. We will search for reasons of a greater expresivity of the Czech translation.